REALIZING THE BLESSING ACCOUNTING AND CREATE UNIQUE PRODUCTS IN EFFORTS TO IMPLEMENT ISLAMIC ECONOMICS IN LUENG PUTU, PIDIE JAYA, ACEH - Harley Agustian; Fajriah; Usman Boini; Fazil; Husni Rahmah; Zulaiva Ulya; Muhammad Syukur (RADJA PUBLIKA, 2024)
Blessing Accounting is a financial report and business activity transactions that are in accordance with Islamic law, the Qur'an and As-Sunnah. Efforts to maintain the stability and development of a business are by maintaining and managing a good and correct financial system, not only paying attention to large profits but also the important value of blessings measured in each transaction. This service aims to realize the implementation of blessing accounting while creating unique products, this is to implement Islamic economic values ​​in the Pidie Jaya area, Aceh. Participants in this activity were 21 students at the Lueng Putu Pidie Jaya Islamic boarding school. The method of activity used was the lecture or counseling method, education and training, case studies and field surveys, practice of finding unique products and application of blessing accounting. The results of this community service show that around 90% of students are able to understand and apply the concept of Islamic economic values ​​in the application of blessing accounting in business transactions, this is important because after completing their education, the students will spread and preach to convey important information about the truth in transacting according to sharia so that blessings in their business are born and more goodness increases in their business.